2015
DOI: 10.3233/jpd-150652
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI Correlates of Episodic Memory Processes in Parkinson’s Disease Without Mild Cognitive Impairment

Abstract: Background Changes in episodic memory are common early in Parkinson’s disease (PD) and may be a risk factor for future cognitive decline. Although medial temporal lobe (MTL) memory and frontostriatal (FS) executive systems are thought to play different roles in distinct components of episodic memory impairment in PD, no study has investigated whether different aspects of memory functioning are differentially associated with MTL and FS volumes in nondemented patients without mild cognitive impairment (PD-woMCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
4
12
2
Order By: Relevance
“…As for group differences in brain volume, only frontal lobe volume was significantly reduced in the PD group, contrary to other studies of PD without MCI ( Tessitore et al, 2012 ; Baggio et al, 2015 ; Pirogovsky-Turk et al, 2015 ; Harrington et al, 2017 ). Despite this finding, smaller parietal, temporal, and occipital volumes were associated with stronger right DLPFC-left middle/inferior temporal connectivity only in PD participants.…”
Section: Discussioncontrasting
confidence: 99%
“…As for group differences in brain volume, only frontal lobe volume was significantly reduced in the PD group, contrary to other studies of PD without MCI ( Tessitore et al, 2012 ; Baggio et al, 2015 ; Pirogovsky-Turk et al, 2015 ; Harrington et al, 2017 ). Despite this finding, smaller parietal, temporal, and occipital volumes were associated with stronger right DLPFC-left middle/inferior temporal connectivity only in PD participants.…”
Section: Discussioncontrasting
confidence: 99%
“… 42 Results on RBMT novel task showed that PD patients perform poorer than controls, too. As commonly recognized, 43 PD patients demonstrate impaired free recall due to disruption of strategies for search and retrieve of information, presumably due to an executive dysfunction in this case. This finding is consistent with the fact that people with frontal lobe dysfunction report poor performances in recall tasks, especially in delayed ones after interfering activities.…”
Section: Discussionsupporting
confidence: 58%
“…In specific domains, we noted that the levels of the miR-29s family were all associated with the z-score of memory function. As PD-NC progresses to PDD, studies have shown that memory deficits become apparent, implicating a supervening dysfunction of temporal lobe storage mechanisms [ 18 ]. This association between miR-29s and memory function may result from the high expression of miR-29s in the central nervous system, particularly in neurons of the hippocampus [ 14 ].…”
Section: Discussionmentioning
confidence: 99%